2019
DOI: 10.1016/j.ekir.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Paying for Hemodialysis in Kerala, India: A Description of Household Financial Hardship in the Context of Medical Subsidy

Abstract: Introduction: Many low-and middle-income countries are implementing strategies to increase dialysis availability as growing numbers of people reach end-stage renal disease. Despite efforts to subsidize care, the economic sustainability of chronic dialysis in these settings remains uncertain. We evaluated the association of medical subsidy with household financial hardship related to hemodialysis in Kerala, India, a state with high penetrance of procedure-based subsidies for patients on dialysis. Methods: Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Probably they were more aware and better users of available services. [24] We understand that even among them the long term management of kidney disease will be difficult. In the background of very high prevalence of diabetes and hypertension we need clinical research to find out a screening test for early detection at primary levels and suggest life style modifications and provision of specific anti hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…Probably they were more aware and better users of available services. [24] We understand that even among them the long term management of kidney disease will be difficult. In the background of very high prevalence of diabetes and hypertension we need clinical research to find out a screening test for early detection at primary levels and suggest life style modifications and provision of specific anti hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…For many ESKD patients, particularly elderly patients in the COVID era, assisted PD may be more optimal than in-center HD, potentially reducing exposure risk for infection in transit or within the clinic itself. HD treatment is financially unattainable in many countries and recognized as universally financially distressing in a recent study in India 26. A study from New Zealand interviewed 52 patients with advanced CKD and their caregivers, confirmed that economic concerns are often present, strong, and underreported 27.…”
mentioning
confidence: 94%
“…In this issue of Kidney International Reports , Bradshaw et al. 3 address whether economic subsidies for patients with end-stage renal disease on dialysis in Kerala, India, impact catastrophic health expenses or distress financing. This question is especially relevant given that many countries have chosen to cover dialysis as a benefit under the premise that doing so will not only improve the lives of patients but also be more efficient for the health care system as a whole by reducing the number of emergency and hospitalization expenses.…”
mentioning
confidence: 99%